Inovasi Pengelolahan Produk Minuman Es Lumut Jelly untuk Meningkatkan Kreativitas Kewirausahaan Mahasiswa - Muhammad Sinar Randi; Anggi Annisa Pohan; Nita Hayati; Nabila Dwirizki Handayani; Rahmania Hasibuan (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
Es Lumut Jelly is a simple soft drink with three main ingredients, namely milk, jelly and a variety of flavors which are given the latest innovation in bottle packaging. This moss ice jelly drink is in great demand by many age groups. Therefore, as a form of innovation in the ice moss jelly drink, the author provides additional ingredients such as various flavor variants. The method in this research uses qualitative research. Qualitative research aims to gain an in-depth understanding of the observed phenomena. In this research, the researcher acts as the main instrument in collecting descriptive data. With innovation in processing simple beverage products, students can increase their creativity in entrepreneurship. By increasing creativity, students are able to process various flavors and create better economic opportunities.